QUESTION OF HARMONIZATION OF CRIMINAL LIABILITY FOR THE TERRORIST ACTION UNDER THE INTERNATIONAL CONTRIBUTIONS OF UKRAINE - Петриченко, Олег Пилипович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article analyzes the problematic aspects of the harmonization of Article 258 of the Criminal Code of Ukraine with international normative-legal acts, reveals the disadvantages of the disposition of this article, the reasons 5and conditions for their occurrence. Methods of research: in the work the dialectical method of cognition, general scientific and special methods was used. Results: a new version of Article 258 of the Criminal Code of Ukraine was proposed. The statistics and experience of the application of this article in practice are shown, emphasizing the urgency of creating the legal grounds for counteracting terrorism in modern conditions. The article analyzes the crime provided for in Article 258 of the Criminal Code of Ukraine, the subject and object, the objective and subjective aspect. The disadvantages of disposition of this article, reasons and conditions of their occurrence are revealed. First of all, emphasis was placed on overloading the disposition of Article 258 of the Criminal Code of Ukraine with superfluous phrases and details. Secondly, it is indicated on the mistaken use of alternative signs of such crime as intimidation of the population and influence. Separately, attention is drawn to the unsuccessful use of the term «terrorist act» in Article 258 of the Criminal Code of Ukraine. The discrepancy between this term and the terminology used in the Convention and the Additional Protocol to it is proved. The expediency of replacing this term with others is substantiated - an «act of terrorism». The proposals of some scientists concerning the improvement of this article are analyzed. The expediency of demarcation of terrorist acts depending on their commission in peacetime and in wartime is substantiated. It is proposed to supplement the article with a note where to define «significant property damage». Discussion: search for ways to improve the implementation of the provisions of international legal acts in the Criminal Code of Ukraine.